Investigation of the effect of alpha-aluminum oxide nanoparticles addition to UV-curable resin for 3D printing: Material characterization and mechanical properties analysis - Ali H. Al-helli; Ali N. Alobiedy (Results in Engineering)
In this research, we tried to study the printer's ability to handle high additive ratios, starting with adding 5 wt. % of aluminum oxide nanopowder and incrementing by 5 wt. % to research the maximum ratio of the printer, 30 wt. %. At this ratio, many printing problems appeared. In the end we got six groups (without adding, 5, 10, 15, 20, or 30 wt. %). The process of printing the samples included adding the nanopowder to the mixture and mixing them using a hand mixer, a magnetic stirrer, and then an ultrasonic mixer. Scanning electron microscopy device (SEM) results indicated that the particles that were added were spread out evenly, with no agglomeration or porosity between them. Energy Dispersive X-Ray Analysis (EDX) results showed that the samples have the elements (carbon, nitrogen, and oxygen) of the liquid UV resin and the appearance of the aluminum element and the increase in the percentage of oxygen in the modified samples. The X-ray Diffraction (XRD) results indicated that the resin did not crystallize. Furthermore, we investigated the compressive strength, microhardness, and wear rate of the prepared samples. These additions enhance the mechanical properties of the commercial UV resin. The best results were 383 MPa with a 29 % increase at 20 wt. % enhancement, 231.2 MPa with a 24 % increase at 30 wt. % enhancement, and 0.024 mm⁴/N with a 39 % decrease at 5 wt. % additive nano powder for stress peak, micro hardness, and wear resistance, respectively.